Impact of community-based interventions on HIV knowledge, attitudes, and transmission - Salam, Rehana A (BioMed Central, 2014)
In 2012, an estimated 35.3 million people lived with HIV, while approximately two million new HIV infections were reported. Community-based interventions (CBIs) for the prevention and control of HIV allow increased access and ease availability of medical care to population at risk, or already infected with, HIV. This paper evaluates the impact of CBIs on HIV knowledge, attitudes, and transmission. We included 39 studies on educational activities, counseling sessions, home visits, mentoring, women’s groups, peer leadership, and street outreach activities in community settings that aimed to increase awareness on HIV/AIDS risk factors and ensure treatment adherence. Our review findings suggest that CBIs to increase HIV awareness and risk reduction are effective in improving knowledge, attitudes, and practice outcomes as evidenced by the increased knowledge scores for HIV/AIDS (SMD: 0.66, 95% CI: 0.25, 1.07), protected sexual encounters (RR: 1.19, 95% CI: 1.13, 1.25), condom use (SMD: 0.96, 95% CI: 0.03, 1.58), and decreased frequency of sexual intercourse (RR: 0.76, 95% CI: 0.61, 0.96). Analysis shows that CBIs did not have any significant impact on scores for self-efficacy and communication. We found very limited evidence on community-based management for HIV infected population and prevention of mother- to-child transmission (MTCT) for HIV-infected pregnant women. Qualitative synthesis suggests that establishment of community support at the onset of HIV prevention programs leads to community acceptance and engagement. School-based delivery of HIV prevention education and contraceptive distribution have also been advocated as potential strategies to target high-risk youth group. Future studies should focus on evaluating the effectiveness of community delivery platforms for prevention of MTCT, and various emerging models of care to improve morbidity and mortality outcomes.